Assessing the Cytotoxic Effects of Calcium Hydroxide and Triple Antibiotic Paste on SCAP: A Systematic Review - Jyotsana Singh; P.Nihar; Ritik Kashwani; Neetu Jhunjhunwala; Sooriaprakas Chandrasekaran; Anukriti Kumari (The Bioscan, 2025)
Aim: This systematic review paper focuses on the effects of two common intracanal medicaments used in regenerative endodontic procedures on the survival of human apical papilla cells. Background: Periapical lesions form due to an inflammatory response triggered by microorganisms and their by-products invading the root canal system. Endodontic therapy aims to eliminate these microbes and disinfect the root canal system. Reducing the microbial load is crucial before obturation, as it helps alleviate symptoms and reduces the incidence of persistent periapical pathosis. This study aims to evaluate and compare the effects of calcium hydroxide and triple antibiotic paste (TAP) intracanal medicaments on the survival of human apical papilla cells. Materials & Methods: An electronic search of the Medline database (via PubMed) and Web of Science was conducted using terms such as calcium hydroxide, TAP, and intracanal medicaments. The search criteria followed the PRISMA statement guidelines. For each selected study, data were extracted: Study design and methodology, Sample size and characteristics, and Type and concentration of intracanal medicament used. Results: Twenty articles met the established criteria and were included.